SIKAP SOPAN SANTUN ANAK DILIHAT DARI POLA ASUH ORANG TUA TUNGGAL - Reza Nur Faizah; Nur Fajrie; Ratri Rahayu (Universitas Muria Kudus, 2021)
Parenting is a treatment or way of educating parents in order to meet the needs and educate children in everyday life. In a family, the presence of parents is very important for the development of a child's personality, because the family is the first and foremost environment that will influence several aspects of child development, including the child's polite attitude. But not all children have complete parents, there are some children who are so unlucky that they only have one parent. But how to educate single parents is not much different from parents who are intact in instilling child courtesy. The cultivation of polite attitudes given by single parents to children is to provide understanding of what is good and bad and to give good examples to their children, so that children are more accustomed to seeing good things and can be imitated by children in everyday life. In this article, we will describe the polite behavior of children seen from the parenting styles applied by single parents